The Effect of Problem Based Learning Models and Levels of Creativity Toward Student Outcomes in Vocational High School - Dasining, Dasining; Muslim, Supari; Handajani, Sri (International Journal for Educational and Vocational Studies, 2019)
This study aims to determine the level of creativity of students who are taught using problem based learning models and students who are taught using direct learning models. To find out the learning outcomes of students who have a high level of creativity and creativity level of creativity is low. The method used in this study is Quasi Experimental. The design used is a 2x2 factorial design, because this design can be used to see student learning outcomes before administering treatments and after giving treatments. The results of the study found: (1) the level of creativity of students who study using a learning model based on higher learning outcomes compared to students who learn with the direct learning model; (2) student learning outcomes with a high level of creativity, significantly higher than students who have low levels of creativity; and (3) there is an interaction between the use of learning models and the level of creativity on student learning outcomes. This study concludes that: (1) problem based learning models can improve student creativity; (2) students who have a high level of creativity, higher learning outcomes than students who have low levels of creativity; and (3) there is an interaction between the use of learning models and the level of creativity on student learning outcomes.